2014
DOI: 10.1021/ef402300k
|View full text |Cite
|
Sign up to set email alerts
|

Downhole Heavy Crude Oil Upgrading Using CAPRI: Effect of Steam upon Upgrading and Coke Formation

Abstract: Heavy crude oil and bitumen are characterized by a low yield of light distillates in the range of 10–30% with a boiling point below 350 °C, high density (low API gravity), high viscosity, and high heteroatom content, which impede their exploitation. In this study, the catalytic upgrading process in situ (developed by the Petroleum Recovery Institute, Canada) add-on to the toe-to-heel air injection for the extraction and upgrading of heavy oil and bitumen downhole was investigated. The effect of steam addition … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
29
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 44 publications
(32 citation statements)
references
References 33 publications
2
29
1
Order By: Relevance
“…The analysis was performed with a ramp temperature increase from 25 to 900°C under air flow of 50 mL·min −1 . A detailed description of these analytical instruments has been reported elsewhere [3,6,7]. The products are grouped into coke, liquid and noncondensable gas yields after the upgrading reaction and are calculated by the following Eqs.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The analysis was performed with a ramp temperature increase from 25 to 900°C under air flow of 50 mL·min −1 . A detailed description of these analytical instruments has been reported elsewhere [3,6,7]. The products are grouped into coke, liquid and noncondensable gas yields after the upgrading reaction and are calculated by the following Eqs.…”
Section: Methodsmentioning
confidence: 99%
“…The use of an activated carbon guard bed on top of the catalyst has been reported to reduce coke formation and sustain catalyst lifetime by removal of coke precursors and the addition of hydrogen promotes hydroconversion reactions which are shown to deposit less coke than thermal cracking [3,6,7]. Moreover, in situ hydrogen production from steam via the water-gas-shift reaction has also been investigated as a source of hydrogen to promote hydrocracking and hydrogenation reactions by Hart et al [7]. It was found that both hydrogen-addition and steam improved API gravity and viscosity of the produced oil and reduced coke formation.…”
Section: Introductionmentioning
confidence: 99%
“…Upgrading in situ gives a cleaner production of less viscous oil, which is more easily transported without the use of diluents (Shah et al, 2010). The THAI-CAPRI (Toe-to-Heel Air Injection coupled with Catalytic Upgrading Process In situ) technology combines thermally enhanced oil recovery with down-hole catalytic upgrading of heavy oil into light fractions (Greaves and Xia, 2004;Hart et al, 2014). This catalytic upgrading, using steam, hydrogen and methane, showed significant improvements over non-catalytic thermal processes (Hart et al, 2014).…”
Section: Upgrading Of Fossil Oilsmentioning
confidence: 99%
“…The THAI-CAPRI (Toe-to-Heel Air Injection coupled with Catalytic Upgrading Process In situ) technology combines thermally enhanced oil recovery with down-hole catalytic upgrading of heavy oil into light fractions (Greaves and Xia, 2004;Hart et al, 2014). This catalytic upgrading, using steam, hydrogen and methane, showed significant improvements over non-catalytic thermal processes (Hart et al, 2014). Conventional cracking catalysts such as supported noble metals are prohibitively expensive; one economic option could utilize regenerated catalysts from treated oils but these have lower activity (Hart et al, 2014).…”
Section: Upgrading Of Fossil Oilsmentioning
confidence: 99%
“…More recent studies have shown the potential for rapid catalyst deactivation due to coke and metal deposits during the catalytic upgrading and possibilities to overcome the challenges of coke deposits by addition of hydrogen or a hydrogen donor [6]. In addition to the above methods, another promising direction is the use of sub-micron catalysts for chemical processes to upgrade heavy oil and bitumen in-situ [7].…”
Section: Introductionmentioning
confidence: 99%